Systematic Literature Review: Metode Deteksi Dini Diabetes Mellitus Gestasional - Rizky Vaira; Merlin Karinda (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Gestational Diabetes Mellitus (GDM) is one of the medical complications of pregnancy that can cause short-term and long-term risks for the mother and fetus if not detected early and treated appropriately. This study aims to find, select, assess, extract, and synthesize data from several articles on the method of early detection of GDM that can be carried out by health workers. This study uses a systematic literature review method with the PICO framework. Search articles using PubMed and Science Direct databases with keywords and Boolean operators in this study are "early detection" or "screening" and "gestational diabetes mellitus" and "pregnant woman" or “pregnant mother”. Research articles published in 2016–2021, in English, research design: using a quantitative research design. The results of the study found that early detection of GDM can be done through a scoring system, identification of women's diet before pregnancy and optimization of early GDM screening before 24 weeks, monitoring growth and improving early detection services for gestational diabetes in basic health facilities. Health workers need to provide education to women of reproductive age about GDM, so that when they decide to get pregnant they can understand the importance of maintaining blood sugar levels.